EFEKTIVITAS BAHAN AJAR BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN KEMANDIRIAN BELAJAR DAN PEMAHAMAN KONSEP IPA SISWA - Nur'aeni, Amellia Putri; Pranoto, Yuli Kurniawati Sugiyo; Avrilianda, Decky; Ellianawati (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
The purpose of this study is to analyze the effectiveness of augmented reality (AR)-based teaching materials in enhancing students' understanding of science concepts and their independent learning skills in the subject of Natural Sciences (IPA) at Karawang Kulon II Elementary School. The methodology applied in this study is quantitative, incorporating a one-group pretest-posttest experimental design. Data collection involved administering written tests and questionnaires to assess students' conceptual understanding and learning independence. Results reveal that the average score achieved in the pretest for students was 64.2, while the average posttest score increased to 77.95, with the gain test indicating a substantial improvement. Additionally, the questionnaire results indicate that students' learning independence is categorized as very good, with a percentage of 90%. These findings highlight that the use of AR contributes to a better understanding of science concepts among students and supports their independent learning efforts. This research contributes meaningfully to the enhancement of innovative and effective teaching methods, while also offering educators insights for designing more engaging and interactive educational experiences.